Mycoflora and Incidence of Aflatoxin in Wheat Seeds from Duhok Province, Kurdistan Region of Iraq - Bazyani, Lina F.; Saadullah, Asia A.M. (Science Journal of University of Zakho, 2018)
Identification of fungi that contaminated wheat grains and their aflatoxins production were investigated in Thirty-three samples collected from different sources in Duhok province, Kurdistan region of Iraq during 2014-2015. In this study a total of twenty-five species belonged to 12 genera was isolated and identified on DRBC, MEA and PDA media. Nine distinct species were identified within Aspergillus which revealed highest diversity among all isolated genera. Followed by five species of Penicillium.Alternariacame after which showed only two species. Two teleomorphic ascomycota Emericella, and Eurotiumwere recorded. The results showed that A. nigerand A. flavuswere the most isolated species. Aflatoxin production potential detected by A. flavusand A. parasiticus were screened using ELISA method. Aflatoxin potential detected in culture of Aspergillus flavus isolates was ranged from 57 to 310 ppb, while, the potential production aflatoxin for A. parasiticus isolates were ranged from 189 – 450 part per billion.